BIOETHICS IN THE QUALITY OF THE MEDICAL SERVICE OF GRADUATES IN LINKAGE WITH SOCIETY - González, MSC Ada María; Nader, PHD Jorge Daher (International Journal of Research -GRANTHAALAYAH, 2022)
Offering good quality in health services in our country and in the world is essential. Inculcate this importance in students and develop in them an awareness that allows them to establish a correct Doctor-Patient Relationship, based on the Universal Principles of Bioethics: Autonomy, Beneficence, Non-Maleficence and Justice. This article is the result of an investigation, which raises the importance of the quality of services and how it should be carried out by doctors graduated from the University of Guayaquil in their relationship with the Society. It highlights certain key points and requirements that the doctor must meet in order to have a satisfactory quality of service provided in the Doctor-Patient relationship. Obtaining as results a guide or protocol of action, governed in the form of points that all doctors must carry out to fulfill the fundamental objective of achieving an efficient Doctor-Patient relationship and offering high Quality in Health Services. The training and professionalization of our Graduates in Health Sciences require Quality, a Rigorous, Complex, Holistic, Challenging preparation; that marks the difference between a Professional and an Amateur of Medicine